Anxiety disorders in adolescents - E. A. Korabelnikova (Медицинский совет, 2018)
Anxiety disorders are considered as the most common class of mental disorders of adolescence. Anxiety affects all areas of a teenager’s life, significantly worsening his state of health, school performance indicators and relationships in the family and society. The article describes the characteristics of anxiety disorders in the adolescent period from the position of etiopathogenesis, classification, clinical features. The need for an integrated approach to the therapy of anxiety disorders in adolescents is grounded, which includes, in addition to full-fledged pharmacotherapy, a wide range of psychotherapeutic, physiotherapeutic and social rehabilitation activities.